1993
DOI: 10.1055/s-0038-1649685
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Plasminogen Activators and Plasminogen with Heparin: Effect of Ionic Strength

Abstract: SummaryIn order to define the possible effects of heparin on the fibrinolytic system under physiological conditions, we studied the interactions of this drug with plasminogen and its activators at various ionic strengths. As reported in recent literature, heparin stimulated the activation of Lys-plasminogen by high molecular weight (HMW) and low molecular weight (LMW) two-chain urokinase-type plasminogen activator (u-PA) and two-chain tissue-type plasminogen activator (t-PA) 10- to 17-fold. Our results showed,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

1995
1995
2003
2003

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…Most of the above studies were performed at subphysiological ionic strengths of buffers and the results were inconsistent because of the variations in the ionic strengths of the buffers used. Interaction of heparin with Lys-plasminogen was reported to be salt sensitive while binding of t-PA to heparin-agarose was less salt sensitive [27]. Glu-Plg, but not t-PA, was reported to bind with fucoidan-sepharose [19].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Most of the above studies were performed at subphysiological ionic strengths of buffers and the results were inconsistent because of the variations in the ionic strengths of the buffers used. Interaction of heparin with Lys-plasminogen was reported to be salt sensitive while binding of t-PA to heparin-agarose was less salt sensitive [27]. Glu-Plg, but not t-PA, was reported to bind with fucoidan-sepharose [19].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies by Liang et al [26] suggested that the stimulation of t-PA activity by heparin was probably due to a direct binding of heparin to t-PA, causing a conformational change of t-PA and making it more accessible to plasminogen interaction. Single chain t-PA is reported to bind with high affinity to heparin-agarose [27] and the heparin binding sites on t-PA have been located on the finger and kringle 2 domains [36]. The results of affinity chromatography using fucoidan-Sepharose showed a high degree of affinity between fucoidan and Glu-Plg while t-PA did not bind with fucoidan-Sepharose [19].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…u-PA does not contain the typical HP-binding consensus sequence reported by Cardin and Weintraub (15), although it seems to bind to HP through the kringle domain of its aminoterminal fragment (ATF), where several basic amino acid residues are found (16 -19). There is also evidence that the u-PA B-chain and the u-PA catalytic site participate in u-PA/HP interactions (19,20). Moreover, injection of HP in mice increases the fibrinolytic activity in the plasma euglobulin fraction by an increase of u-PA protein levels, probably following u-PA elution from endothelial cells (21).…”
mentioning
confidence: 99%